Fasilitasi Ibu-ibu PKK Kelas Menengah Desa Wagir Kidul dalam Pelatihan Facial - Melani Candra; Fuad Fitriawan (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Wagir Kidul has a village government structure as well as village organizations, one of which is the PKK, which is attended by women. The PKK in the village of Wagir Kidul consists of 22 members who often hold meetings to discuss PKK programs, from an economic, religious, health and so on perspective. As is the case in Wagir Kidul village, from the various potentials, most of the PKK women in Wagir Kidul village, especially the middle class PKK women, middle class here means mothers with a moderate economy, meaning not unemployed but have potential, interests and also costs to work in the field of beauty. Most of these PKK women work as teachers, there are also midwives, or female students where they are only productive in the morning while other time is not used by doing patent activities. Many of them don't understand how to choose skincare and use it properly. In this case, the best way to be able to take good care of your face is by means of facial treatment.The purpose of this study was to facilitate middle-class PKK mothers in Wagir Kidul village in facial training. The method used in this research is the Asset Based Community Driven (ABCD) method, which is a method that emphasizes the development of assets owned by communities in an area. As a result, the facilitation that has been carried out has had a positive impact on participating PKK mothers. This was indicated by the high enthusiasm of the PKK mothers. In addition, the PKK mothers who participated in the training admitted that they understood more about using and choosing beauty products and had side business opportunities such as salons and beauty clinics.